PENGEMBANGAN MEDIA PEMBELAJARAN â€œPIGAM TAPEâ€ BERBASIS MACROMEDIA FLASH 8 MATERI MENGIDENTIFIKASI LAMBANG/SIMBOL SISWA KELAS III SEKOLAH DASAR - Azlina, Nur; Mujiwati, Endang Sri; Damariswara, Rian (TARBAWI:Journal on Islamic Education, 2023)
The objectives of this research are: 1) knowing the validity; 2) knowing the effectiveness; and 3) knowing the responses of teachers and students to the learning media "PIGAM TAPE" based on macromedia flash 8 material identifying symbols/symbols of grade III elementary school students. The method used in this research is the development method (RnD) with the ADDIE development model. Data collection techniques using tests and questionnaires. While the data analysis technique uses quantitative and qualitative data analysis. The results of the research on the development of learning media "PIGAM TAPE" based on macromedia flash 8 material to identify symbols for grade III elementary school students are as follows: (1) declared very valid by meeting the criteria for the percentage of media validity of 89% and material validity of 93.3%, (2) declared good based on the teacher's response by meeting the percentage criteria of 94%, while the results of student responses in the limited trial received a percentage of 100% and in the broad trial received a percentage of 95%, and (3) declared effective by meeting the percentage of classical learning completeness of the student test of 100%. Based on these results, it can be concluded that the PIGAM TAPE learning media is declared very valid and feasible to use in learning Indonesian language on the material of symbols of traffic signs.